PENENTUAN OOIP (ORIGINAL OIL IN PLACE) LAPANGAN X BERDASARKAN METODE MATERIAL BALANCE PLOT DAN RECOVERY FACTOR DIANALISIS BERDASARKAN DRIVING MECHANISM PLOT - Fansuri, Taufik
OOIP (Original Oil In Place) can be calculated using several methods. One of the methods is the material balance method. This method requires data from PVT analysis, reservoir properties, and production history. Beside OOIP determining, material balance method can be used to determine drive index values. Based on these values, the type of driving mechanism which works dominantly in the reservoir can be identified. After identification, the calculated RF (Recovery Factor) of the reservoir is compared with RF value from literature. This study calculates drive index of X field to evaluate OOIP obtained from material balance calculation. The evaluation is carried out by comparing RF (Recovery Factor) at present with a common value of RF found in the literature.